2020
DOI: 10.1007/s12192-020-01078-0
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of HSP70 by VER-155008 synergistically enhances bortezomib-induced cytotoxicity in multiple myeloma

Abstract: Proteasome inhibitor bortezomib is one of the most effective drugs currently available for the treatment of multiple myeloma (MM). However, the intrinsic and acquired resistance to bortezomib can limit its effectiveness. The activation of heat shock response has been characterized as a potential resistance mechanism protecting MM cells from bortezomib-induced cell death. In this study, in response to bortezomib therapy, we discovered that HSP70 is one of the most substantially upregulated heat shock proteins. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…Additionally, pan-HSPA inhibitors showed synergy with certain anticancer drugs. Their combination with bortezomib, a first-in-class proteasome inhibitor used as an oncological drug, showed synergistic effects on NSCLC cells in vitro [26] and in multiple myeloma in vitro and in vivo models [34,35]. Triple combination of HSPA inhibitor with cisplatin and 17-AGG, a HSPC inhibitor, showed a synergistic effect on bladder cancer cells [32].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, pan-HSPA inhibitors showed synergy with certain anticancer drugs. Their combination with bortezomib, a first-in-class proteasome inhibitor used as an oncological drug, showed synergistic effects on NSCLC cells in vitro [26] and in multiple myeloma in vitro and in vivo models [34,35]. Triple combination of HSPA inhibitor with cisplatin and 17-AGG, a HSPC inhibitor, showed a synergistic effect on bladder cancer cells [32].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple myeloma patients often experience acquired resistance to bortezomib [138]. Hence, a combination of targeted therapies seems to be possible method, such as inhibiting the known compensatory mechanisms to proteasome inhibition, such as activation of HSP70/HSP90 molecular chaperones or autophagy [139][140][141], or targeting the NRF2-mutant p53-miRNA axis to counteract the proteasome inhibitor resistance [38,39].…”
Section: Cellular Proteasome Machinerymentioning
confidence: 99%
“…These findings confirmed that sRAGE might be a protective role in bone progression [73]. Huang et al [74] investigated in MM cell lines (RPMI 8226, OPM2, and MM.1S) the effects of bortezomib, the first therapeutic proteasome inhibitor recommended for the first-line treatment in refractory, relapsed, and newly diagnosed MM. It has been postulated that the activation of the heat shock response may be one of the mechanisms by which MM does not respond or partially responds to bortezomib.…”
Section: Hmgb1-induced Chemoresistancementioning
confidence: 66%